Alzheimer’s disease may develop from changes in the immune system, cell cycle, and protein processing following alterations in ribosome function - Akiko Yamakawa; Mutsumi Suganuma; Risa Mitsumori; Shumpei Niida; Kouichi Ozaki; Daichi Shigemizu (Scientific Reports)
Abstract The prevalence of Alzheimer’s disease (AD) is increasing as society ages. The details of AD pathogenesis have not been fully elucidated, and a comprehensive gene expression analysis of the process leading up to the onset of AD would be helpful for understanding the mechanism. We performed an RNA sequencing analysis on a cohort of 1227 Japanese blood samples, representing 424 AD patients, 543 individuals with mild cognitive impairment (MCI), and 260 cognitively normal (CN) individuals. A total of 883 and 1169 statistically significant differentially expressed genes (DEGs) were identified between CN and MCI (CN-MCI) and between MCI and AD (MCI-AD), respectively. Pathway analyses using these DEGs, followed by protein–protein interaction network analysis, revealed key roles of ribosomal function in MCI progression, whereas immune responses, cell cycle, and protein processing in endoplasmic reticulum were involved in AD progression. Our findings indicate that the onset of AD might be associated with gene expression changes in the immune system, cell cycle, and protein processing following alterations in the expression of ribosomal protein genes during the MCI stage, although validation using brain tissue samples will be necessary in the future. Given the known effectiveness of delaying MCI progression in preventing AD, the genes related to ribosomal function might emerge as biomarkers for early diagnosis.